2019
DOI: 10.1371/journal.pone.0210491
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the insecticidal activity of double-stranded RNA targeting the smooth septate junction of western corn rootworm (Diabrotica virgifera virgifera)

Abstract: The western corn rootworm (WCR, Diabrotica virgifera virgifera) gene, dvssj1, is a putative homolog of the Drosophila melanogaster gene, snakeskin (ssk). This gene encodes a membrane protein associated with the smooth septate junction (SSJ) which is required for the proper barrier function of the epithelial lining of insect intestines. Disruption of DVSSJ integrity by RNAi technique has been shown previously to be an effective approach for corn rootworm control, by apparent suppression of production of DVSSJ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…These findings support that the malfunction of SSJ complexes in the midgut triggered by DvSSJ1 RNAi were the main effects leading to the death of WCR. The DvSSJ1 is a midgut-specific gene in WCR and its functions are consistent with the biological functions described for Drosophila 9 . Two forms of transgenic DvSSJ1 dsRNAs present in plant tissues are long dsRNAs and siRNAs 8 .…”
supporting
confidence: 80%
See 3 more Smart Citations
“…These findings support that the malfunction of SSJ complexes in the midgut triggered by DvSSJ1 RNAi were the main effects leading to the death of WCR. The DvSSJ1 is a midgut-specific gene in WCR and its functions are consistent with the biological functions described for Drosophila 9 . Two forms of transgenic DvSSJ1 dsRNAs present in plant tissues are long dsRNAs and siRNAs 8 .…”
supporting
confidence: 80%
“…from WCR 9 . These proteins play a crucial role in maintaining tissue homeostasis through the regulation of stem cell proliferation and enterocyte behavior in the Drosophila adult midgut 11 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In western corn rootworm, Hu et al (2016) identified another target gene-mesh (alternatively named dvssj2) which encodes a smooth septate junction protein important for structural integrity of the midgut epithelium. They showed that silencing mesh impairs midgut barrier function which results in increased larval mortality (Hu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%